2011
DOI: 10.3146/ps10-3.1
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive NIR Reflectance Spectroscopic Method for Rapid Fatty Acid Analysis of Peanut Seeds

Abstract: Near Infrared Reflectance Spectroscopy (NIRS) was used to rapidly and nondestructively analyze the fatty acid concentration present in peanut seeds samples. Absorbance spectra were collected in the wavelength range from 400 nm to 2500 nm using NIRS. The oleic, linoleic and palmitic fatty acids were converted to their corresponding methyl esters and their concentrations were measured using a gas chromatograph (GC). Partial least square (PLS) analysis was performed on a calibration set, and models were developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…NIR reflectance spectroscopy is proven to be an important nondestructive proximate analysis of oil and fatty acid composition in peanut seeds (Sundaram et al, ). As the NIR spectra are influenced by unwanted signal variation from various sources such as light scattering, temperature or particle sizes, spectra were pretreated by second derivative for making spectral absorbance band clearer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NIR reflectance spectroscopy is proven to be an important nondestructive proximate analysis of oil and fatty acid composition in peanut seeds (Sundaram et al, ). As the NIR spectra are influenced by unwanted signal variation from various sources such as light scattering, temperature or particle sizes, spectra were pretreated by second derivative for making spectral absorbance band clearer.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been successfully applied for breeding for altered fatty acid profile in soybean (Hurburgh, ; Sato & Kawano, ), sunflower (Vich, Velascob, & Martinez, ), almond (Cuesta, Fernández‐Martínez, Company, & Velasco, ), rapeseed‐mustard (Kim, Park, Choung, & Jang, ; Kumar, Chauhan, & Kumar, ), and peanut (Lee et al, ). Sundaram et al () suggested that reflectance derivative model is better than absorbance‐based model for the prediction of fatty acid profile in peanut seeds. In the present study, the reflectance‐based data (in duplicate) was collected from a new noncalibrated NIR spectrophotometer (DA 7200; Perten Instrument).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that NIR data performed somewhat better than the mid-IR data [17]. NIRS has been used extensively to analyze oil content and fatty acid profile in oilseeds such as sunflower [18], rapeseed [19], soybean [20], peanut [21], and castor [22], as well as in other commodities such as cereals [23], forages [24], corn [25], and animal products [26]. Conversely, NIRS has not yet been reported for evaluation of most soybean essential nutrients like tocopherols, saponins, FAs, and flavonoids.…”
Section: Introductionmentioning
confidence: 95%
“…NIRS allows fast spectrometric measurement of several traits in a single analysis provided that the corresponding calibration equations are available. NIRS have been extensively used to analyze oil content and fatty acid profile in oilseeds such as sunflower 10, rapeseed 11, soybean 12, peanut 13, and castor 14, as well as in other commodities such a cereals 15, forages 16, or animal products 17. However, little research has been conducted in tree nuts.…”
Section: Introductionmentioning
confidence: 99%